Громадські організації в СРСР : доктринальні дослідження Ц. А. Ямпольської - Волкова Дарія Євгенівна; Волкова Дарья Евгеньевна; Volkova Dariya (My University, 2013)
This article is dedicated to the constitutional study of the Z.A.Yampolskaya’s works on the constitutional status of NGOs. Ms. Yampolskaya, born 1914, was the outstanding researcher of the Soviet times - Doctor of Law, Professor, Honored Scientist of the RSFSR. Based on a comprehensive study of her books, the provisions that can be used in modern Ukrainian by the science of constitutional law were found.
Волкова Д. Є. Громадські організації в СРСР : доктринальні дослідження Ц. А. Ямпольської / Д. Є.Волкова // Науковий вісник Міжнародного гуманітарного університету : Серія «Юриспруденція». – 2013. – Вип.6-2. - Т.1. – С.66-70.
Keywords: громадські об’єднання; громадські організації; свобода асоціацій; СРСР; общественные объединения; общественные организации; свобода ассоциаций; СССР; civic associations; non-governmental organizations; freedom of association; the USSR